Effect of carbon nanotube location and dispersed phase on the dielectric properties of polypropylene/high‐density polyethylene/carbon nanotube nanodielectrics. Issue 29 (21st May 2022) - de Carvalho, Diego; Becker, Daniela; Dalmolin, Carla
Abstract: The effect of carbon nanotube location and dispersed phase on the dielectric properties of nanocomposites with carbon nanotubes (CNTs) and polypropylene/high‐density polyethylene (PP/HDPE) blends was investigated. Different compatibilizers styrene‐ethylene‐buthylene‐styrene copolymer (SEBS), ethylene‐propylene‐diene‐methylene rubber (EPDM), and ethylene‐propylene copolymer (EP) were used. In order to obtain a smaller HDPE phase, 0.1%(w/w) of CNT was added to a PP/HDPE (90/10) blend with 3%(w/w) of compatibilizer. Samples were processed in a twin‐screw extruder with a controlled sequential mixing based on thermodynamic (using the wetting parameter, ω AB ) and kinetic parameters (such as melting temperature and melting flow indices). FESEM images show the formation of nanoblends for all compositions, with a dispersed morphology with HDPE droplets with a diameter of about 100 nm (measured with ImageJ© software) inside the PP matrix, and TEM images show the CNTs present in both phases. However, compatibilizers seemed to expel the nanoparticles from the dispersed phase, which may have contributed to a reduction of the dielectric constant of the CNT nanocomposites. Dielectric properties were evaluated through Impedance Spectroscopy, showing that CNTs contribute to the interfacial polarization and constant dielectric rise from 3.15@1 Hz (without CNTs) to 16.91@1 Hz (with CNTs, but no compatibilizer). Abstract :